Using the medication adherence reasons scale (MAR-scale) to identify the reasons for non-adherence in Chinese hypertensive patients - Jingjing Pan; Bin Hu; Xiaorong Xue; Lian Wu (PLoS ONE, 2025)
Objectives This study aimed to determine the prevalence of medication non-adherence and to explore the factors influencing it among Chinese hypertensive patients. Patients and methods A total of 571 hypertensive patients hospitalized in a tertiary hospital in Xi’an, China were invited to participate in this cross-sectional study. The Chinese Version of Medication Adherence Reasons Scale (ChMAR-Scale) was used to identify the most common reasons for non-adherence to hypertension medications.Binary logistic regression analysis was employed to analyze independent risk factors for adherence in hypertensive patients.Descriptive statistics were used to calculate the adherence rates and trends in the reasons for non-adherence. Results Approximately 66.9% of the patients did not adhere to their medications.Age (adjusted odds ratio [AOR] = 0.976, 95%CI:0.955–0.998, P = 0.032),education level(AOR = 0.566, 95% CI:0.419–0.765,P < 0.001) and blood pressure (BP) categories (AOR = 0.580, 95% CI: 0.439–0.767,P < 0.001) were independently associated with hypertensive medication adherence. Belief issues and self-perception issues were identified as the main reasons for medication non-adherence.These included self-adjustment of medications according to BP or physical condition, checking whether the medicine was still needed, concerns about long-term effects, and the belief that there was no longer a need to take the medicine. Conclusion Poor medication adherence is widespread among Chinese hypertension patients. More attention should be paid,and effective strategies should be developed to address the factors affecting treatment adherence.These factors include certain sociodemographic factors,such as age,education level and BP categories as well as belief issues and self-perception issues of hypertensive patients. The findings of this study can potentially assist healthcare providers in formulating targeted interventions to improve medication adherence.